Azaphthalocyanines: Red Fluorescent Probes for Cations. Issue 16 (19th March 2013) - Novakova, Veronika; Lochman, Lukáš; Zajícová, Ivana; Kopecky, Kamil; Miletin, Miroslav; Lang, Kamil; Kirakci, Kaplan; Zimcik, Petr
<x xml:space="preserve">Abstract</x> Light up a red crown: Chelation of sodium and potassium cations by aza[15]crown‐5 switches on strong red fluorescence in azaphthalocyanines. This is due to an inhibition of ultrafast intramolecular charge transfer by coordination of the cations to the donor center. Sodium cations fit well into a cavity of the recognition moiety, while potassium forms supramolecular assemblies of azaphthalocyanines with 1:2 stoichiometry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>